(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Adenoid cystic carcinoma (ACC) is a rare malignant tumor that can manifests as proptosis in adult population. They account for 1.6% of all orbital tumors. Despite their rarity, they are the second most frequent epithelial neoplasms occurring in the lacrimal gland after pleomorphic adenomas. This kind of tumors are commonly occur in the salivary glands but can metastasize to lung, breast ,brain and sinuses in hematogenous route.We describe a patient who presented with protrusion of right eyeball, developing over 8 years with history of intermittent watery discharge for 4 years. His magnetic resonance imaging showed a retrobulbarextraconal soft tissue lesion around the lacrimal fossa with invasion and erosion of the adjacent bone. The patient underwent right sided orbito-pterional craniotomy and gross total removal of tumor. Pathologic analysis showed neoplastic cells in a predominantly cribriform pattern with features of perineural invasion and diagnosed as a case adenoid cystic carcinoma of the lacrimal gland. We review the incidence, clinical features, radiographic and histopathologic features of these rare, aggressive malignancies along with current treatment options with reference to the relevant literatures. Bang. J Neurosurgery 2019; 9(1): 49-53